Vulval angiomyxoma: a case report - Misra, Sujata; Rath, Tanushree Sandipta; Nayak, B. L.; Giri, Sushil Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Aggressive angiomyxoma is a rare, locally invasive mesenchymal tumor occurring usually in women of reproductive age, which carries a high risk for local relapse; hence it needs to be differentiated from other mesenchymal tumors occurring in this region. We describe a case of a 39-year-old female presenting with a large swelling on the left labia majora. Initially she presented as a small mass over left labia majora 2 years ago from which biopsy was taken which came as acute inflammatory (suppurative) lesion on histopathological report. Now she presented with a mass of 14×10 cm over left labia majora, left perineal region, protruding into the left vaginal wall as well. Clinical examination revealed mass over vulvo-perineal region with variegated appearance and soft to firm in consistency. On per vaginum examination, the mass was extending upto the level of ischiorectal fossa. FNAC of the mass was done and the cytological report came out to be fibrolipoma. In view of benign nature of huge mass, the patient was planned for excision. Gross examination of specimen showed tumour dimensions of 30 cm×14 cm× 10cm. Final histopathology revealed it to be a case of Aggressive Angiomyxoma.